Hakikat Kebahagiaan Hidup: Konsensus antara Al-Qur’an dan Filsafat Stoikisme - Taufik Rahman; Lola Pertiwi; Ariyandi Batubara (Jurnal Riset Agama, 2022)
This study aims to find a consensus between the Qur'an and stoic philosophy about the happiness of life. The concept of happiness which varies in each individual, gives birth to different solutions. The discourse on happiness in the Stoics has become an actual thing among millennials today. This research uses a descriptive-analytical method with a qualitative approach and literature review as the main reference source. The results and discussion in this study found that there are similar indicators in achieving happiness between the Qur'an and the philosophy of stoicism. This study concludes that the Qur'an and the philosophy of stoicism are not two contradictory things, amor fati (love of destiny) and emotional control taught by the Stoic philosophers as well as the concepts of gratitude and patience in the terminology of the Qur'an. This shows that the Qur'an and philosophy have a common concept that can be met.